DIGITALISASI LAYANAN DITINJAU DARI MODAL INTI, BIAYA OPERASI TEÍHADAP PENDAPATAN OPERASI DAN KINEÍJA KEUANGAN BANK - Ahmad Basri; Noorchamid Ustadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to examine the effect of core capital and operating costs on operating income on bank financial performance with service digitalization as a dummy variable. This research uses three independent variables, namely core capital, operating costs to operating income and digitalization of services. The population in this study are banking companies listed on the Indonesia Stock Exchange for the 2019-2022 observation period. The data used in this research is secondary data obtained from financial data on the website www.idx.com. Digitalization of services also influences the financial performance of a bank. Technology has an influence on bank performance, because technology can help carry out banking activities. The digitalization of services that occurs in Indonesia cannot be avoided because it is in line with the development of existing information and communication technology and to face competition from FinTech companies, realizing the importance of digitizing services, this research was conducted to examine the influence of digitalization of services on banking financial performance. Core capital (tier 1 capital) has no effect on bank financial performance. Operating costs to operating income (BOPO) have a negative effect on bank financial performance. The BOPO value which decreases from year to year indicates an increase in efficiency thereby improving a company's financial performance and the digitalization of services has a positive effect on bank financial performance.